If it's not what You are looking for type in the equation solver your own equation and let us solve it.
x-15=-2x+3
We move all terms to the left:
x-15-(-2x+3)=0
We get rid of parentheses
x+2x-3-15=0
We add all the numbers together, and all the variables
3x-18=0
We move all terms containing x to the left, all other terms to the right
3x=18
x=18/3
x=6
| P=9x-14 | | 4(y+2)-8+4y=32+2(2y-4) | | 4x+14=x+14 | | 3(x+1)=9-2x | | 16w+7w-16=-81 | | 11x=8x−3(5−2x) | | 12.3+6=p | | 2x-19=21-3x | | 11x+3x+7=21 | | 5v-2v=-v+12 | | Y=-60x+240 | | 5=j-7 | | d-11=15 | | 2(5x+1)=8x+2 | | 1=d-5 | | 3k-5-4k=3+7k | | x+4(-0.5x+8)=18 | | 5(x-2)-3x=12 | | 2x^+7x=4x+9 | | 24=y+12 | | 279+15x=360+12x | | 43x+15=360 | | 2(c+1)=c+1 | | 3x+4x=34 | | 43x+12-4+12+-5=360 | | 0.18x+0.13(50)=0.16(x+50) | | 39+2x=6x-9 | | 5y+24=8y | | 5=c-2 | | 360+12x=279+12x | | -18+8n=20+6n | | x-4=33 |